Genomic analysis of chromosomal cointegrated blaNDM-1-carrying ICE and blaRSA-1-carrying IME from clinical multidrug resistant Aeromonas caviae - Luo, Xinhua; Yin, Zhe; Yu, Lianhua; Zhang, Jin; Hu, Dakang; Xu, Mengqiao; Wang, Peng; Wang, Fengling; Feng, Jiao (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The objective of this study is to thoroughly analyze the detailed genomic characteristics of clinical strain 211703 of Aeromonas caviae, which co-carrying blaRSA-1 and blaNDM-1 genes. 211703 was isolated from the patient’s cerebrospinal fluid drainage sample in a Chinese tertiary hospital. Methods Carbapenemase NDM was detected by the immunocolloidal gold technique. The MIC values were determined by VITEK2. The whole genome sequence of 211703 was analyzed using phylogenetics, genomic comparison, and extensive dissection. Results This study revealed that 211703 only contained a single 4.78 Mb chromosome (61.8% GC content), and no plasmids were discovered in 211703. 15 different types of resistant genes were detected in the genome of 211703, including blaRSA-1 harbored on integrative and mobilizable element (IME) Tn7413a, and blaNDM-1 harbored on integrative and conjugative element (ICE). The ICE and IME were all carried on the chromosome of 211703 (c211703). Detailed comparison of related IMEs/ICEs showed that they shared similar conserved backbone regions, respectively. Comprehensive annotation revealed that blaRSA-1 was carried by the gene cassette of a novel integron In2148 on Tn7413a, and blaNDM-1 was captured by an insertion sequence ISCR14-like on the ICE of 211703. We speculated that mobile genetic elements (MGEs) such as ICE and IME facilitated the spread of resistance genes such as blaRSA-1 and blaNDM-1. Discussion In conclusion, this study provides an overall understanding of the genomic characterization of clinically isolated A. caviae 211703, and an in-depth discussion of multiple acquisition methods of drug resistance genes in Aeromonas. To the best of our knowledge, this is the first report of A. caviae carrying blaRSA-1 even both blaRSA-1 and blaNDM-1, and this is the first bacterium carrying blaRSA-1 isolated from the clinical setting.